Influence of material distribution and damping on the dynamic stability of Bernoulli-Euler beams - Garus, Sebastian; Garus, Justyna; Sochacki, Wojciech; Nabiałek, Marcin; Petru, Jana; Borek, Wojciech; Šofer, Michal; Kwiatoń, Paweł (Bulletin of the Polish Academy of Sciences Technical Sciences, 2023)
The study analyzed the influence of materials and different types of damping on the dynamic stability of the Bernoulli-Euler beam. Using the mode summation method and applying an orthogonal condition of eigenfunctions and describing the analyzed system with the Mathieu equation, the problem of dynamic stability was solved. By examining the influence of internal and external damping and damping in the beam supports, their influence on the regions of stability and instability of the solution to the Mathieu equation was determined.